Expression profiles of miR-129 and miR-29a-5p in vascular calcification of patients with end-stage renal disease and the underlying correlation: miR-129 and miR-29a-5p expression in vascular calcification - Sheng, Yuping; Ma, Xiaoying; Wang, Na; Yang, Xingmeng; Zhang, Haoran; Xu, Haiping; Sun, Fuyun (Cellular and Molecular Biology, 2022)
To analyze the changes and correlation of Mir-129 and Mir-29A-5p in vascular calcification in end-stage renal disease. A total of 97 patients with end-stage renal disease admitted to our hospital from August 2021 to August 2020 were selected as the research objects, and another 97 healthy people who underwent physical examination in our hospital during the same period were selected as the control study. According to X-ray examination, 97 subjects were divided into the vascular calcification group (39 cases) and the non-vascular calcification group (58 cases). Blood samples were extracted from each group, and the expressions of serum Mir-129 and Mir-29A-5p were detected by RT-PCR after centrifugation. The expressions of Mir-129 and Mir-29A-5p in healthy people with end-stage renal disease and vascular calcification were analyzed. To analyze the correlation of Mir-129 and Mir-29A-5p in vascular calcification of end-stage renal disease and its correlation with vascular calcification of end-stage renal disease. Compared with healthy people, the expression of Mir-129 and Mir-29A-5p in patients with the end-stage renal disease was abnormally increased, and there was a difference between the two groups (P<0.05). The expression levels of Mir-129 and Mir-29A-5p in patients with end-stage renal disease without vascular calcification were lower than those in the vascular calcification group, and there were differences between the two groups (P<0.05). Compared with mild vascular calcification, mir-129 and Mir-29A-5p expressions were higher in moderate and severe vascular calcification patients. In addition, compared with moderate patients, the expressions of Mir-129 and Mir-29a-5p were lower in mild patients and higher in severe patients. The expressions of Mir-129 and Mir-29A-5p in patients with mild and moderate vascular calcification were lower than those in patients with severe vascular calcification, and there were differences among the three groups (P < 0.05). Mir-129 and Mir-29A-5p were positively correlated with vascular calcification in end-stage renal disease (R =5.426, P=0.001). Mir-129 was positively correlated with vascular calcification in end-stage renal disease (r=0.649, P=0.001). Mir-29a-5p was positively correlated with vascular calcification in end-stage renal disease (r=0.529, P=0.001). Mir-129 and Mir-29a-5p showed high expression in the patients with end-stage renal disease, and they also increased with the occurrence of vascular calcification, and they showed a positive correlation in the vascular calcification of end-stage renal disease.